Green Village Tourism in Indonesia: Regulation, Development and Challenges - Wibowo, Dwi Edi; Nur, Muhammad (Lembaga Contrarius Indonesia, 2024)
Tourism is essential to economic growth and development at the national, sectoral, and local levels. Almost all regions face conflicts of interest in the management of tourism and tourist villages, stemming from the inability of tourist location managers to balance all interests with frequently over lapping regulations and policies. This research aims to examine and analyze the authority of the village government in regulating and managing tourist villages based on ecological justice in villages around the Borobudur Temple area, exploring the regulatory model for managing tourist villages based on ecological justice in villages around the Borobudur Temple area. The study employs a sociological-legal approach that prioritizes field research. Data sources consist of primary legal materials obtained through interviews, secondary legal materials obtained from literature, and tertiary legal materials. The data analysis method employs a variety of techniques. The research results indicate that the village government around the Borobudur temple area has the authority to manage and regulate tourist villages. This authority includes preparing tourist village development plans, granting business permits, regulating tourism activities, developing human resources, and collaborating with related parties. The proposed tourism village management model is a setting that focuses on ecological justice: community participation, environmental management, local economic empowerment, education, and environmental awareness. Ecological justice-based tourism villages must ensure equitable distribution of economic, social, and environmental benefits among all local community members, including vulnerable and marginalized groups.